‘Multi-stressed’: A qualitative study exploring the impact of the social determinants of health on access to digital mental health for youth and young adults in Alberta - Lia Norman; Katherine Bright; Emilie M Bassi; Marianne Barker; Julia Hews-Girard; Karina Pintson; Sarah Daniel; Lauren Volcko; Simron Sidhu; Katelyn Greer; Jason Gondziola; Leanne Stamp; et al. (Digital Health, 2025)
Background Mental illness among youth (ages 15–24) is a critical and global public health issue. Youth's pathways to accessing mental healthcare are complex, non-linear, and mediated by the social determinants of health – including social, economic, environmental, and systemic factors. Digital mental health is recognised as a potential solution to address inequitable access to mental healthcare among youth. However, concerns have been raised regarding access to digital mental health for youth who are underserved and excluded by current mental healthcare systems. Access to digital mental health is a matter of mental health equity requiring urgent attention. Methods This study explores mental healthcare providers’ perspectives of how the social determinants of health affect access to digital mental health for youth in Alberta, Canada. A qualitative descriptive methodology was utilised to analyse focus group data and identify pertinent themes. Results Twenty-three focus groups were conducted with 168 participants from schools, specialised mental health services, primary care networks, and community-based mental health service settings. Findings show that youth's access to digital mental health is impacted by three overarching and intersecting themes: (1) social influences, (2) socio-economic circumstances, and (3) community contextual and systemic factors. Conclusions The three themes indicate that the social determinants of health do not occur in isolation and may combine to produce multiple forms of disadvantage. Practical considerations and recommendations emphasise the need to address the social determinants of health to ensure that all youth benefit equitably from emerging digital solutions.